Virulent Fusarium isolates with diverse morphologies show similar invasion and colonization strategies in alfalfa - Yang, Jian; Han, Jing; Jing, Yuqing; Li, Siyang; Lan, Bo; Zhang, Qian; Yin, Kangquan (Frontiers in Plant Science, 2024)
Root rot is a major disease that causes decline of alfalfa production, and Fusarium is a major pathogen associated with root rot. In this study, 13 Fusarium isolates were obtained from alfalfa with root rot in Gansu Province, the major alfalfa production region in China. The isolates were characterized by molecular genotyping (ITS, TEF 1- and RPB2 fragments) and identified as six species, which included the F. acuminatum, F. incarnatum, F. oxysporum, F. proliferatum, F. redolens, and F. solani. We found that their morphology varied significantly at both the macro-and micro-levels, even for those from the same species. We developed a low cost and fast pathogenicity test and revealed that all isolates were pathogenic to alfalfa with typical root rot symptoms such as leaf yellowing and brown lesions on the root and stem. However, the virulence of the isolates differed. We also found that the conidia of all isolates germinated as early as 24 hours post inoculation (hpi), while hyphae colonized the root extensively and invaded the xylem vessel by 48 hpi. Together our results reveal that different virulent Fusarium isolates use a similar invasion strategy in alfalfa. This natural plant-fungus pathosystem is intriguing and warrants further examination, particularly with regard to efforts aimed at mitigating the impact of multiple similar vascular pathogens on infected alfalfa plants.